`Wide and emergent - narrow and focussed`: A dual-pathway approach to talent identification and development in England Rugby Union - Till, K.; Barrell, D.; Lawn, J.; Lazenby, B.; Rock, A.; Cobley, S. (Talent identification and development in sport. International perspectives, 2021)
England RU has a structure for youth rugby known as age-grade rugby (England Rugby, 2019a), whereby players participate within annual-age categories (e.g., under 13 years of age). The national governing body, the Rugby Football Union (RFU), governs age-grade rugby, with participation occurring alongside identification and development of young talented players. Based on research and a unique Talent Symposium event (Rugby Football Union, 2013), the RFU developed a wide and emergent as well as narrow and focussed talent identification and development pathway. This chapter provides an overview of (1) the key findings and messages from the Talent Symposium (Rugby Football Union, 2013), (2) the RFUs talent identification and development system, and (3) the benefits and challenges of deploying a wide and emergent as well as narrow and focussed pathway.